Análise de crédito e risco bancário: crédito bancário como fator dependente do risco socioambiental - Dzioubanov, André Osowski (Universidade do Vale do Rio dos Sinos, 2015)
This paper proposes to identify aspects inherent to corporate social responsibility and environmental management of organizations, coupled to the economic and financial data, to bank credit analysis. An overview of the evolution of the credit market is made and related to the concepts of credit and bank credit risk. The paper also proposes identifying in the literature review, a study of the procedures used by a large private bank for analysis for the feasibility analisys of providing credit and risks involved. Regarding the methodology, it is a qualitative and exploratory research through indirect documentation and a questionnaire as a data collection tool for thus compare it to the credit risk policy of this financial institution. Through this study, it was possible to conclude that the environmental issue it is a concern and conclude that the credit lending is dependent on the social and environmental risk by changing subjectively the concept and the level of risk assigned to the client.
Keywords: Avaliação de empresas; Critérios econômicos; Crédito; Risco socioambiental; Instituição financeira; Company valuation; Economic criteria; Credit; Environmental risk; Financial institution